Comparing the web and mobile platforms of a social Q&A service from the user's perspective. Issue 2 (20th March 2018) - Chen, Xiaoyu; Chua, Alton Y.K.; Deng, Shengli
Abstract : Purpose: As an increasing number of users have acquired information across the web and mobile platforms for social question and answering (Q&A), it is of interest to explore whether there are differences in social Q&A usages between the two platforms. The purpose of this paper is to compare web and mobile platforms of a social Q&A service from the user's perspective in terms of three dimensions, namely, demographics, individual-based constructs, and information-based constructs. Design/methodology/approach: Because Zhihu.com is one of the most popular social Q&A sites in China, the authors used online questionnaires to investigate its users' perceptions of these three dimensions. From January to March 2016, the authors obtained 278 valid responses in total through snowball and convenient sampling. Collected data are analyzed through descriptive statistics and inferential statistics. Findings: The results indicate that there exist significant differences between web users and mobile users on Zhihu.com in terms of gender, affinity, and information seeking. More specifically, compared to the male users, more female users rely on the mobile platform to access the information service; mobile users perceive higher affinity with Zhihu.com than web users; and mobile users perceive higher information-seeking intention than web users do. Originality/value: Regarding the theoretical aspect, this study proposes a conceptual framework for comparison between the web and mobile platforms of social Q&A from the user's perspective. Regarding the practical aspect, the comparative results of this study could give social Q&A service providers useful information about users' differences between web and mobile platforms of social Q&A services.